SOLID FUEL FROM EMPTY FRUIT BUNCH FIBER AND WASTE PAPERS PART 4: COMPRESSION TEST AT LATERAL POSITION - YAAKOB, MOHD YUHAZRI; HASOLOAN, HAERY IAN PIETER; YAHAYA, SAIFUDIN HAFIZ; SAID, MD RADZAI (getview, 2012)
This research discussed on the results obtained for each sample that have been conducted to the solid fuel briquettes made of empty fruit bunch fiber and waste papers from view of mechanical performance which is compression test at lateral position test. This solid fuel prepared by manual compression technique and tested using universal testing machine. This analysis important to know the capability of solid fuel to sustained external force because of mechanical activities. Experimental work shows that, the larger amount of paper in the ratio, the higher the maximum load it can withstand before failure, therefore briquette S/N 6 gives the highest compressive strength.